[tex] {y}^{2} = 52y - 576 \\ = > {y}^{2} - 52y + 576 = 0 \\ = > {y}^{2} - 36y - 16y + 576 = 0 \\ = > y(y - 36) - 16(y - 36) = 0 \\ = > (y - 36)(y - 16) = 0 \\ = > y = 16 \: \: or \: \: 36[/tex]
[tex] {y}^{2} - 34x + 289 = 0 \\ = > {(y)}^{2} - 2 \times y \times 17 + {(17)}^{2} = 0 \\ = > {(y - 17)}^{2} = 0 = > y - 17 = 0 \\ = > y = 17[/tex]
[tex] {x}^{2} - 8x - 84 = 0 \\ = > {x}^{2} - 14x + 6x - 84 = 0 \\ = > x(x - 14) + 6(x - 14) = 0 \\ = > (x + 6)(x - 14) = 0 \\ = > x = - 6 \: \: or \: \: 14[/tex]
[tex] {y}^{2} = 4y + 96 \\ = > {y}^{2} - 4y - 96 = 0 \\ = > {y}^{2} - 12y + 8y - 96 = 0 \\ = > y(y - 12) + 8(y - 12) = 0 \\ = > (y + 8)(y - 12) = 0 \\ = > y = - 8 \: \: or \: \: 12[/tex]
Hope you could get an idea from here.
Doubt clarification - use comment section.